National Survey of Pharmacy Practice at MOH Hospitals in Saudi Arabia 2016: Pharmacy Education and Training - Alomi, Yousef Ahmed; Alghamdi, Saeed Jamaan; Alattyh, Radi Abdullah (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia 2016-2017: Pharmacy Education and Training. Methods: It is a 4-months cross-sectional National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia. The study consisted of two parts; the demographic information and the second part contained eighty-five questions divided into nine domains drove from American Society of Health-System Pharmacists (ASHP) and Saudi Pharmaceutical Society (SPS) survey, the international standard of Joint Commission of Hospital Accreditation in addition to the local standards of Saudi Center of healthcare accreditation. An electronic questionnaire distributed to the one hundred eighty-five directors of pharmacies at MOH hospitals. The study discussed and analyzed National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia: the drug monitoring and patient’s education. All analysis were done through survey monkey system. Results: The survey questionnaire was distributed to 185 hospitals, the rate of reply, was 105 (56.75%). The most hospital pharmacies required a continuing medical education (CME) 62 (59 %), and allowed paid time off for continuing education program was 45 (42.9%). The policy of CME existed in 47 (44.8%) only while not lived in 58 (55.2%) hospital pharmacies. The most affiliated training program was the pharmacy technician student training program 55 (52.4%) with a total number of candidates (258) annually, and pharmacy students training program 43 (41%) with a total number of candidates was (281) annually. A followed by the on the job training of pharmacy technician program 33 (31.4%) with the total of candidates was (206) annually. The majority of Education and Training available for pharmacy staff for pharmacy technician, pharmacists, and director of the pharmacy, while most Education and Training available delivered to Healthcare professional by pharmacy staff were nurses, general physician, and nursing supervisors. The most courses delivered to health care providers by hospital pharmacies were basic medication safety, Cardiopulmonary resuscitation drugs, and an emergency medicine. Conclusion: The hospital pharmacies had an adequate education and training services for pharmacists and pharmacy technicians while missed by Pharm D student and post-graduate residency programs. Review of strategies for pharmacy education and training is highly recommended.
Keywords: Pharmacy education; Training; Ministry of Health; Saudi Arabia